2020
DOI: 10.1101/2020.09.23.310201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virus-host interactions shape viral dispersal giving rise to distinct classes of travelling waves in spatial expansions

Abstract: Reaction-diffusion waves have long been used to describe the growth and spread of populations undergoing a spatial range expansion. Such waves are generally classed as either pulled, where the dynamics are driven by the very tip of the front and stochastic fluctuations are high, or pushed, where cooperation in growth or dispersal results in a bulk-driven wave in which fluctuations are suppressed. These concepts have been well studied experimentally in populations where the cooperation leads to a density-depend… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
(147 reference statements)
1
2
0
Order By: Relevance
“…4), confirming our main prediction. Although it was not presented in connectivity terms, a similar result was recently found using a model inspired by phage–bacteria interactions (Hunter et al 2020), where reduced connectivity was de facto achieved using increased densities of phage–resistant bacteria as a barrier. In our simulations, these pushed expansions are characterized by a mean dispersal rate independent of population density; this means they would likely converge to a pulled wave as K tends to infinity and the effects of discreteness and stochasticity become negligible.…”
Section: Discussionsupporting
confidence: 56%
“…4), confirming our main prediction. Although it was not presented in connectivity terms, a similar result was recently found using a model inspired by phage–bacteria interactions (Hunter et al 2020), where reduced connectivity was de facto achieved using increased densities of phage–resistant bacteria as a barrier. In our simulations, these pushed expansions are characterized by a mean dispersal rate independent of population density; this means they would likely converge to a pulled wave as K tends to infinity and the effects of discreteness and stochasticity become negligible.…”
Section: Discussionsupporting
confidence: 56%
“…In the current context of habitat loss and fragmentation, several studies have set to explore how habitat connectivity can affect range expansion speeds and/or the evolution of dispersal and other traits during range expansions (Gralka & Hallatschek, 2019; Hunter et al, 2021; Lutscher & Musgrave, 2017; Pachepsky & Levine, 2011; Urquhart & Williams, 2021; Williams, Snyder, et al, 2016; Williams, Kendall, et al, 2016; Williams & Levine, 2018). For instance, using experimental expansions, Williams et al (2016) showed that evolution had stronger effects on range expansion speeds in patchier landscapes where connectivity was lower (or, conversely, that evolution dampened the negative effects of low connectivity on speed).…”
Section: Introductionmentioning
confidence: 99%
“…An experimental platform for studying viral expansion must be able to probe the complex virus-host interactions. A team led by Diana Fusco of the University of Cambridge in the UK has now developed such a platform and applied it to study the waves of viral expansion in an infected cell population [1].…”
mentioning
confidence: 99%